The boss baby [videorecording (DVD)] (20th Century Fox Home Entertainment, 2017)
It is a hilariously universal story about how a new baby's arrival impacts a family, told from the point of view of a delightfully unreliable narrator, a wildly imaginative seven-year-old named Tim. With a sly, heart-filled message about the importance of family, it is an authentic and broadly appealing original comedy for all ages.